Security Utilization of Cloud Computing in The World of Business For Small Medium Enterprises (SMEs) - Fachmi Tamzil; Nizirwan Anwar; Muhammad Abdullah Hadi (International Journal of Science, Technology & Management, 2022)
At this time the business world began to compete globally with the aim of satisfying customers, so companies need access and information that is fast and accurate. To access information quickly, companies need to build information and communication technology infrastructure which is certainly not easy with the need for a large enough capital, besides that there is cloud computing which can be an alternative. The progress of information and communication technology that we have achieved now has really been recognized and felt to provide a lot of convenience and comfort for human life. Information Technology (IT) solutions, cloud computing, are now starting to be discussed a lot by business people, including in Indonesia. Even though it's popular, it doesn't mean cloud computing is easily accepted. Cloud computing will actually save business operations much more, compared to using traditional methods among Small and Medium Enterprises (SMEs). There are various kinds of services provided by cloud computing, including hardware, infrastructure, platforms, and applications. Cloud computing has considerable benefits, this is because the services of cloud computing can reduce computing costs, increase reliability and provide considerable opportunities for the infrastructure world. The purpose of this research is to increase business competitiveness in the business sector by using the Salesfoorce App Cloud application. The results of this application can make business models more flexible and know market needs and consumer needs.